1978
DOI: 10.1177/000456327801500131
|View full text |Cite
|
Sign up to set email alerts
|

Butanol Extraction of Serum and Urinary Gamma-Glutamyltransferase and its Application in Clinical Diagnosis

Abstract: Summary Gamma-glutamyltransferase (γ-GT) activity was measured in serum and urine before and after extraction with n-butanol. Residual γ-GT activity after extraction of normal serum with butanol was more than 75 %, whereas for normal urine the figure was less than 68 %. The loss of activity from urine was not affected by prior dialysis, and the stabilisation which resulted from adding bovine serum albumin at a concentration of 40 g/l did not approach the residual activity with normal serum. In patients with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1978
1978
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…34 In a study of 98 patients with RA, 12 showed increases of both alkaline phosphatase and c-glutamyltransferase levels, but isoenzyme alkaline phosphatase studies disclosed that in three of seven patients, an increase in bone isoenzyme was responsible for the rise of alkaline phosphatase. In the others, the liver isoenzyme alone was raised, and in one patient, both were raised.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…34 In a study of 98 patients with RA, 12 showed increases of both alkaline phosphatase and c-glutamyltransferase levels, but isoenzyme alkaline phosphatase studies disclosed that in three of seven patients, an increase in bone isoenzyme was responsible for the rise of alkaline phosphatase. In the others, the liver isoenzyme alone was raised, and in one patient, both were raised.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…(3) The mixture was centrifuged at 1,400 g for 5 min. (4) The lower (aqueous) layer was used for 7-GT activity, and the assay was performed within 30 min of butanol extraction (4). (5) 7-GT activity following butanol extraction was expressed as a percentage of the activity (of the diluted sample) prior to extraction.…”
mentioning
confidence: 99%
“…The apparent molecular size of this fraction can be reduced by various treatments, so that it approaches that of the intermediate-sized form of the enzyme which predominates in serum. These treatments include extraction with organic sol vents or detergents, and so imply the presence of lipid components in the larger 7-glutamyl transferase complexes, a conclusion which has also been reached by other workers (29)(30)(31). It is not yet clear whether association of the enzyme with lipid results exclusively from the nature of its cellular environment or whether this association takes place, or is modified, after release of the enzyme into the circulation.…”
Section: Regulation Of Enzyme Activitymentioning
confidence: 84%